Cashless Economy- Advantages and Challenges - Patidar, Renuka (Journal of Commerce and Trade, 2020)
The central government of India has embarked on the cashless economy. It is the birth of a new era in the nation with life with digital money. This paper is going to conceptualize the meaning of a cashless system. Explains online banking techniques in India, schemes by government to spread the cashless system in India and highlights the challenges of the cashless economy and electronic payment systems. The objective of this study is to examine the significant challenges that are faced by Indians on the way towards cashless. To achieve the objectives of this exploratory type of personal study, interviews will be conducted. Classification-JEL: N35, Y50